2015
DOI: 10.1093/mnrasl/slv070
|View full text |Cite
|
Sign up to set email alerts
|

The dust mass in z > 6 normal star-forming galaxies

Abstract: We interpret recent ALMA observations of z > 6 normal star forming galaxies by means of a semi-numerical method, which couples the output of a cosmological hydrodynamical simulation with a chemical evolution model which accounts for the contribution to dust enrichment from supernovae, asymptotic giant branch stars and grain growth in the interstellar medium. We find that while stellar sources dominate the dust mass of small galaxies, the higher level of metal enrichment experienced by galaxies with M star > 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
197
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 43 publications
19
197
0
Order By: Relevance
“…The importance of dust growth by accretion for the total dust abundance has already been shown for various galaxy samples by many authors (e.g. Dwek et al 2007;Michałowski et al 2010aMichałowski et al , 2010bHirashita & Kuo 2011;Valiante et al 2011;Kuo & Hirashita 2012;Mancini et al 2015;Michałowski 2015). Recent experiments by Rouillé et al (2014) showed that accretion actually occurs in cold environments.…”
Section: Constraint On the Parametersmentioning
confidence: 82%
“…The importance of dust growth by accretion for the total dust abundance has already been shown for various galaxy samples by many authors (e.g. Dwek et al 2007;Michałowski et al 2010aMichałowski et al , 2010bHirashita & Kuo 2011;Valiante et al 2011;Kuo & Hirashita 2012;Mancini et al 2015;Michałowski 2015). Recent experiments by Rouillé et al (2014) showed that accretion actually occurs in cold environments.…”
Section: Constraint On the Parametersmentioning
confidence: 82%
“…We thus conclude that a variable accretion time scale as adopted in our fiducial model is necessary to reproduce the buildup of dust in galaxies (Mattsson 2011;Calura et al 2014;Mancini et al 2015;Schneider, Hunt & Valiante 2016;Wang, Hirashita & Hou 2017). There is a need for short depletion times in the early Universe, but these short depletion times cannot be sustained, otherwise too much dust grows in the low-redshift Universe.…”
Section: Insights From Comparing Model Variantsmentioning
confidence: 89%
“…All model variants predict dust masses approximately 0.5 dex larger than those predicted by our fiducial model for galaxies in this stellar mass range. This is driven by higher efficiencies for the condensation of dust in stellar ejecta in the 'no-acc' and 'high-cond' (2015) at z = 3, 4, and 5, and a compilation of data in Mancini et al (2015) at z = 6 and 7, taken from Kanekar et al (2013), Ouchi et al (2013), Ota et al (2014), Maiolino et al (2015), Schaerer et al (2015), and Watson et al (2015).…”
Section: Dust Masses In Galaxiesmentioning
confidence: 99%
“…Just as we tie the dust destruction timescale in each cell to its local SN rate, we adopt a growth timescale dependent on local gas density and temperature that enables dust to grow more quickly in dense ISM gas. There is evidence that dust growth is particularly dominant over stellar dust production in galaxies above a certain critical metallicity (Inoue 2011;Asano et al 2013a;Mancini et al 2015), and other models have begun to explore the effect of density, temperature, and metallicity variations on local growth timescales (Inoue 2003;Bekki 2015a). While models that employ variable growth timescales sometimes assume a characteristic grain size, grain density, and atom collision sticking efficiency, increasing the number of estimated parameters, in this work we fixed such parameters at typical Galactic values in a manner similar to Equation (12) in Hirashita (2000) in order to capture the essential density and temperature dependence in the growth timescale.…”
Section: Fiducial Parametersmentioning
confidence: 99%
“…A variety of numerical models have been used in previous work to better understand how dust evolves in a galaxy. These include one-and two-zone models (Dwek 1998;Lisenfeld & Ferrara 1998;Hirashita & Ferrara 2002;Inoue 2003;Morgan & Edmunds 2003;Calura, Pipino & Matteucci 2008;Valiante et al 2009;Gall, Andersen & Hjorth 2011a;Yamasawa et al 2011;Asano et al 2013a;Zhukovska 2014;Feldmann 2015), semi-analytic methods (Somerville et al 2012;Mancini et al 2015), and more recently first smoothed-particle hydrodynamical simulations resolving local dust variations (Bekki 2013(Bekki , 2015a). These models include processes like the formation of dust during stellar evolution, dust growth and destruction in the ISM, radiation field effects, and dust-enhanced molecular formation.…”
Section: Introductionmentioning
confidence: 99%